Noonan Syndrome in South Africa: Clinical and Molecular Profiles - Tekendo-Ngongang, Cedrik; Agenbag, Gloudi; Bope, Christian Domilongo; Esterhuizen, Alina Izabela; Wonkam, Ambroise (Frontiers in Genetics, 2019)
Noonan Syndrome (NS) is a common autosomal dominant multisystem disorder, caused by mutations in more than 10 genes in the Ras/MAPK signaling pathway. Differential mutation frequencies are observed across populations. Clinical expressions of NS are highly variable and include short stature, distinctive craniofacial dysmorphism, cardiovascular abnormalities, and developmental delay. Little is known about phenotypic specificities and molecular characteristics of NS in Africa. The present study has investigated patients with NS in Cape Town (South Africa). Clinical features were carefully documented in a total of 26 patients. Targeted Next-Generation Sequencing (NGS) was performed on 16 unrelated probands, using a multigene panel comprising 14 genes: PTPN11, SOS1, RIT1, A2ML1, BRAF, CBL, HRAS, KRAS, MAP2K1, MAP2K2, NRAS, RAF1, SHOC2, and SPRED1. The median age at diagnosis was 4.5 years (range: 1 month – 51 years). Individuals of mixed-race ancestry were most represented (53.8%), followed by black Africans (30.8%). Our cohort revealed a lower frequency of pulmonary valve stenosis (34.6%) and a less severe developmental milestones phenotypes. Molecular analysis found variants predicted to be pathogenic in 5 / 16 cases (31.2%). Among these mutations, two were previously reported: MAP2K1-c.389A>G (p.Tyr130Cys) and PTPN11 - c.1510A>G (p.Met504Val); three are novel: CBL-c.2520T>G (p.Cys840Trp), PTPN11- c.1496C>T (p.Ser499Phe), and MAP2K1- c.200A>C (p.Asp67Ala). Molecular dynamic simulations indicated that novel variants identified impact the stability and flexibility of their corresponding proteins. Genotype-phenotype correlations showed that clinical features of NS were more typical in patients with variants in MAP2K1. This first application of targeted NGS for the molecular diagnosis of NS in South Africans suggests that, while there is no major phenotypic difference compared to other populations, the distribution of genetic variants in NS in South Africans may be different.